Corrosion Under Insulation Testing and Simulation of Insulated Piping - Ab Halim, Mohammad Farhan (IRC, 2017)
Corrosion under insulation (CUI) is, as the name suggests, external corrosion of piping and vessels manufactured from carbon manganese, low alloy, and austenitic stainless steel that occurs underneath externally clad or jacketed thermal or acoustic insulation fundamentally because of the entrance of water. Until the insulation and cladding or jacketing is removed to permit inspection or when leaks to air happen, by its exceptionally nature CUI has a tendency to stay undetected. This study focus on simulation and testing of CUI. The project is involving the standard method of simulation by improve the standard method of simulation by improve and more organize method because of different environment and condition. Thus, the simulation and testing of corrosion under insulation will be aided by studying the corrosion rate of actual plant and compare it with corrosion rate from experimental lab. A laboratory cell set-up was designed and constructed for the simulation of corrosion under insulation (CUI) on a pipe section at elevated temperature. The CUI cell consisted of six carbon steel ring specimens separated by insulation spacers and held together by blind flanged pipe sections on both ends. Thermal insulation which was placed around the testing section provided the annular space to retain the test environment. The ring specimens were used as test electrodes in two separate electrochemical cells. One cell was used as the control while the other was used to test applied protective coatings. Corrosion measurements was made using and mass loss data under isothermal and cyclic wet/dry test conditions. The objective could not be achieved. This is because the experiment could not be finished due to limited resource and time constraints. However, based on the research paper corrosion under insulation can be simulated and the corrosion rate can be investigated in a laboratory cell.